Impact of Screen Media Usage on Early Childhood Development - Malik, Muneeba; Maqbool, Shazia; Ali, Anam; Azhar, Hina; Ullah, Ehsan; Khan, Aisha Farid (Pakistan Armed Forces Medical Journal, 2022)
Objective: To see the impact of screen media usage on early childhood development. Study Design: Cross-sectional study. Place and Duration of study: Developmental Behavioural Paediatrics Department, Children’s Hospital and Institute of Child Health, Lahore Pakistan, from Oct to Dec 2020. Methodology: This study included 100 children with an age range between 15-36 months and divided into two groups. Group-1 was children with communication behaviour disorders (CBD) (n=50), and Group-2 was typically developing (TD)children (n=50). ShaMaq Developmental Screening Tool (SDST) was administered to children to screen their development.Childhood behaviours were rated on a scale of 0-10 on a Behaviour rating scale. Results: Children with CBD had poor eye contact, response to names, poor imitation, poor pointing and poor one-step command following (p<0.001) compared to typically developing children. Children with CBD had poor eating habits (p<0.01),were more restless (p<0.001), and had a developmental delay (p<0.001) on SDST as compared to the other group. In children with CBD, the extent of screen media exposure was significantly correlated with restlessness (p<0.05) and poor pointing(p<0.01). Conclusion: Exposure to screen media at an early age and prolonged use of screens can lead to adverse developmental outcomes and behaviour issues in children. This is more evident in children with CBD than in typically developing children.